Student aid, academic achievement and labor market behavior - Juanna Schrøter Joensen; Elena Mattana (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2017)
How does the financial aid allocation mechanism affect student behavior? We provide a framework for quantifying the impact of financial aid on student debt, academic capital, and labor market outcomes. We specify and estimate a dynamic discrete choice model of simultaneous education, work, and student loan take-up decisions. We use administrative panel data and exploit exogenous variation from the 2001 Swedish Study Aid reform to estimate the model. The reform reduced the cost of working while enrolled, resulting in a 14 percentage points increase in students working during the academic year. The reform also increased (decreased) the cost of borrowing for low (high) earners. This decreased the share of low expected earners not taking up student loans by 2 percentage points, and increased the share of high expected earners taking up the full loan by 2 percentage points. The estimated model enables ex-ante evaluation of various changes to financial aid packages. We find that front-loading debt repayment - by increasing income-contingency or shortening the loan repayment period - reduces debt and lowers academic capital accumulation as students finance more of the college cost by working and less by taking-up loans. Income-contingency of repayments exhibits and elasticity of -0.72 for debt and -0.14 for income at exit, but is marginally decreasing. Changing the grant/loan composition of aid has little impact on human capital accumulation, but large impacts on student debt. This means that the government largely can decide who bears the college cost without affecting human capital accumulation.
Keywords: D90; H52; I21; I22; I28; J22; J24; J31; 330; Student Aid; Education and Labor Market Outcomes; Dynamic Discrete Choice